2023
DOI: 10.1371/journal.pone.0279102
|View full text |Cite
|
Sign up to set email alerts
|

Spatially selective cell treatment and collection for integrative drug testing using hydrodynamic flow focusing and shifting

Abstract: Hydrodynamic focusing capable of readily producing and controlling laminar flow facilitates drug treatment of cells in existing microfluidic culture devices. However, to expand applications of such devices to multiparameter drug testing, critical limitations in current hydrodynamic focusing microfluidics must be addressed. Here we describe hydrodynamic focusing and shifting as an advanced microfluidics tool for spatially selective drug delivery and integrative cell-based drug testing. We designed and fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Combined chemical and mechanical signal gradients on interspersed culture wells were designed to observe the effects of both drug concentration and shear stress on the viability of skin cancer cells and found that high shear stress has a synergistic effect with dosage on cell viability 68 . A co‐flow focusing, three‐channel microfluidic device was created that could direct path and width of a reagent or drug stream to spatially selective regions and the directed removal of only treated cells for further imaging and analysis 69 . A crossed laminar flow microfluidic system that could flow many different cell types to attach to printed microarray islands of Collagen I or antibodies that are then exposed to orthogonal streams of drug treatments enabled the HT assessment of drug and cell type interactions in a single experiment 70 …”
Section: Two‐dimensional High Throughput Cell Culture Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined chemical and mechanical signal gradients on interspersed culture wells were designed to observe the effects of both drug concentration and shear stress on the viability of skin cancer cells and found that high shear stress has a synergistic effect with dosage on cell viability 68 . A co‐flow focusing, three‐channel microfluidic device was created that could direct path and width of a reagent or drug stream to spatially selective regions and the directed removal of only treated cells for further imaging and analysis 69 . A crossed laminar flow microfluidic system that could flow many different cell types to attach to printed microarray islands of Collagen I or antibodies that are then exposed to orthogonal streams of drug treatments enabled the HT assessment of drug and cell type interactions in a single experiment 70 …”
Section: Two‐dimensional High Throughput Cell Culture Systemsmentioning
confidence: 99%
“…68 A co-flow focusing, three-channel microfluidic device was created that could direct path and width of a reagent or drug stream to spatially selective regions and the directed removal of only treated cells for further imaging and analysis. 69 A crossed laminar flow microfluidic system that could flow many different cell types to attach to printed microarray islands of Collagen I or antibodies that are then exposed to orthogonal streams of drug treatments enabled the HT assessment of drug and cell type interactions in a single experiment. 70 2.4 | Potential limitations of 2D and motivation to move to 3D HTS systems Two-dimensional HT culture systems offer robust screening of high numbers of soluble and insoluble effectors on cellular behavior and responses.…”
Section: Microfluidicsmentioning
confidence: 99%